One-Year Outcomes of a Cohort of Renal Transplant Patients Related to BMI in a Steroid-Sparing Regimen. Issue 12 (December 2017) - Bellini, Maria Irene; Koutroutsos, Kostas; Galliford, Jack; Herbert, Paul E.
Abstract : Background: The prevalence of overweight and obese kidney transplant recipients (KTR) has risen in parallel to the obesity epidemic that has affected the general population over the last two decades. At present, there is an ongoing debate regarding the suitability for transplantation of obese patients. Methods: Data were prospectively collected on consecutive single organ KTR transplanted between January 2014 and March 2016. The patients were stratified according to their body mass index (BMI) using the World Health Organization classification. As a measure of allograft function Modification of Diet in Renal Disease, estimated glomerular filtration rate was used at 3, 6, and 12 months posttransplant. Results: We included 370 KTR: 126 of 370 women; median age, 52.7 years (range, 19-77 years), followed up for a median of 19.5 ± 8.6 months. In total, 155 (41.9%) KTR were underweight or of normal BMI at transplant, whereas 148 (40%) were overweight, and 67 (18.1%) were classified as obese (47 [12.7%] class 1, 11 [3%] class 2, 9 [2.4%] class 3). Overweight and obese KTR had a higher incidence of pretransplant diabetes ( P = 0.021), but no difference was found in new-onset hyperglycemia posttransplant ( P = 0.35). There was also no difference in posttransplant hospital length of stay ( P = 0.386). Obese and overweight KTR had a significantly lower estimated glomerular filtration rate than underweight and normal BMI KTR at 3 and 6 months posttransplant, a finding that did not persist at 1 year follow-up. Overall, 23 patients lost their grafts, and 20 patients died during follow-up. Kaplan Meier analysis showed no difference in allograft loss between the different BMI groups (log rank P = 0.7). Conclusions: In this single-center study, which used short-term data, overweight and obese patients were shown not to have inferior outcomes regarding renal function 1 year posttransplant.